Pesticide monitoring and ecotoxicological risk assessment in surface water bodies and sediments of a tropical agro-ecosystem - Carazo Rojas, Elizabeth (2018)
A pesticide monitoring study including 80 and 60 active ingredients (in surface waters and sediments, respectively) was carried out in a river basin in Costa Rica during 2007–2012. A special emphasis was given on the exceptional ecological conditions of the tropical agro-ecosystem and the pesticide application strategies in order to establish a reliable monitoring network. A total of 135 water samples and 129 sediment samples were collected and analyzed. Long-term aquatic ecotoxicological risk assessment based on risk quotient in three trophic levels was conducted. Short-term risk assessment was used to calculate the toxic unit and prioritization of sampling sites was conducted by the sum of toxic units in both aquatic and sediment compartments. Dimethoate (61.2 μg/L), propanil (30.6 μg/L), diuron (22.8 μg/L) and terbutryn (4.8 μg/L) were detected at the highest concentrations in water samples. Carbendazim and endosulfan were the most frequently detected pesticides in water and sediment samples, respectively. Triazophos (491 μg/kg), cypermethrin (71.5 μg/kg), permethrin (47.8 μg/kg), terbutryn (38.7 μg/kg), chlorpyrifos (18.2 μg/kg) and diuron (11.75 μg/kg) were detected at the highest concentrations in sediment samples. The pesticides carbendazim, diuron, endosulfan, epoxyconazole, propanil, triazophos and terbutryn showed non-acceptable risk even when a conservative scenario was considered. Sum TUsite higher than 1 was found for one and two sampling sites in water and sediment compartments, respectively, suggesting high acute toxicity for the ecosystem.